Analysis of Residual Stress and Deformation of Rolling Strengthen Crankshaft Fillet - Han Shaojun; Feng Jikong; Liu Shiquan; Chen Side (MATEC Web of Conferences, 2016)
Based on the analysis of crankshaft fillet rolling process, used ANSYS finite element analysis software to conduct the elastic-plastic mechanical simulation of crankshaft rolling process, and gained the variation law of the residual stress and plastic deformation in the radial path of the fillet under different rolling laps and rolling pressure. Established the relationship between the rolling pressure and the plastic deformation and residual stress of the fillet, and provided theoretical support for the evaluation and detection of the crankshaft rolling quality.